Fabrication of hollow flower-like magnetic Fe3O4/C/MnO2/C3N4 composite with enhanced photocatalytic activity - Mingliang Ma (Nature Portfolio, 2021)
Abstract The serious problems of environmental pollution and energy shortage have pushed the green economy photocatalysis technology to the forefront of research. Therefore, the development of an efficient and environmentally friendly photocatalyst has become a hotpot. In this work, magnetic Fe3O4/C/MnO2/C3N4 composite as photocatalyst was synthesized by combining in situ coating with low-temperature reassembling of CN precursors. Morphology and structure characterization showed that the composite photocatalyst has a hollow core–shell flower-like structure. In the composite, the magnetic Fe3O4 core was convenient for magnetic separation and recovery. The introduction of conductive C layer could avoid recombining photo-generated electrons and holes effectively. Ultra-thin g-C3N4 layer could fully contact with coupled semiconductor. A Z-type heterojunction between g-C3N4 and flower-like MnO2 was constructed to improve photocatalytic performance. Under the simulated visible light, 15 wt% photocatalyst exhibited 94.11% degradation efficiency in 140 min for degrading methyl orange and good recyclability in the cycle experiment.